Assessing the Impact of ISO 21001 Implementation on the Quality and Efficiency of Distance Education at the University - Khairul Tri Anjani; Anna Rufaidah (Universitas Pakuan, 2024)
In the era of digital transformation, distance education plays a pivotal role in expanding equitable access to higher education. Universitas Terbuka, as Indonesia’s leading open and distance learning institution, strives to enhance its service quality and student satisfaction through the adoption of the ISO 21001:2018 Educational Organization Management System. This study explores the implementation process of ISO 21001 at Universitas Terbuka and analyzes its impact on the quality of distance education services. Employing a qualitative case study approach, the research investigates the institution’s strategic initiatives, challenges, and outcomes related to ISO 21001 compliance. The findings reveal that the implementation of ISO 21001 has significantly improved operational efficiency, instructional quality, and student satisfaction. Moreover, it has strengthened organizational accountability and international recognition. This study highlights that the integration of ISO 21001 provides a systematic framework for continuous improvement, aligning institutional goals with global standards of educational excellence. The results are expected to serve as a reference for other higher education institutions seeking to implement ISO-based management systems to achieve sustainable educational quality.